Assessing the Leverage of Islamist Groups and Opposition Parties Alliance in Indonesia’s Regional Electoral Contest - Herdiansah, Ari Ganjar; Gutama, Arie Surya; Sumadinata, Widya Setiabudi (UI Scholars Hub, 2022)
This article tempts to verify the intricate dynamics of political alliances between Islamist groups and opposition parties in Indonesian elections, focusing on the 2018 West Java gubernatorial contest. The study employs exit poll data, investigating the relationship between religiosity, politico-religious narratives, and voting behaviour. While the mobilising power of Islamist groups appeals to political parties, creating a temporary alliance, these do not guarantee electoral triumph even in a conservative region. The politico-religious propaganda, in principle, consolidates Islamist-inclined voters. Despite high levels of religiosity among voters, the alliance's strategies fail to convey this religious mobilisation into broad electoral success. This underscores that the efficacy of such campaigns is contextually dependent and shaped by local socio-political conditions. However, the alliances offer potential political leverage, suggesting an enduring interplay between Islamist groups and political parties in the Indonesian electoral landscape. This exploration contributes to understanding the complexities of Islamist mobilisation within multi-level electoral contests.